Solve for y (5y-1)^(-1/3)-6(5y-1)^(-4/3)=0

Math
(5y-1)-13-6(5y-1)-43=0
Simplify each term.
Tap for more steps…
Rewrite the expression using the negative exponent rule b-n=1bn.
1(5y-1)13-6(5y-1)-43=0
Rewrite the expression using the negative exponent rule b-n=1bn.
1(5y-1)13-61(5y-1)43=0
Combine -6 and 1(5y-1)43.
1(5y-1)13+-6(5y-1)43=0
Move the negative in front of the fraction.
1(5y-1)13-6(5y-1)43=0
1(5y-1)13-6(5y-1)43=0
Find the LCD of the terms in the equation.
Tap for more steps…
Finding the LCD of a list of values is the same as finding the LCM of the denominators of those values.
(5y-1)13,(5y-1)43,1
The LCM is the smallest positive number that all of the numbers divide into evenly.
1. List the prime factors of each number.
2. Multiply each factor the greatest number of times it occurs in either number.
The number 1 is not a prime number because it only has one positive factor, which is itself.
Not prime
The LCM of 1,1,1 is the result of multiplying all prime factors the greatest number of times they occur in either number.
1
The factor for 5y-1 is 5y-1 itself.
(5y-1)=5y-1
(5y-1) occurs 1 time.
The factors for 5y-1 are (5y-1)⋅(5y-1), which is 5y-1 multiplied by itself 2 times.
(5y-1)=(5y-1)⋅(5y-1)
(5y-1) occurs 2 times.
The LCM of (5y-1)13,(5y-1)43 is the result of multiplying all factors the greatest number of times they occur in either term.
(5y-1)43
(5y-1)43
Multiply each term by (5y-1)43 and simplify.
Tap for more steps…
Multiply each term in 1(5y-1)13-6(5y-1)43=0 by (5y-1)43 in order to remove all the denominators from the equation.
1(5y-1)13⋅(5y-1)43-6(5y-1)43⋅(5y-1)43=0⋅(5y-1)43
Simplify 1(5y-1)13⋅(5y-1)43-6(5y-1)43⋅(5y-1)43.
Tap for more steps…
Simplify each term.
Tap for more steps…
Cancel the common factor of (5y-1)13.
Tap for more steps…
Factor (5y-1)13 out of (5y-1)43.
1(5y-1)13⋅((5y-1)13(5y-1)33)-6(5y-1)43⋅(5y-1)43=0⋅(5y-1)43
Cancel the common factor.
1(5y-1)13⋅((5y-1)13(5y-1)33)-6(5y-1)43⋅(5y-1)43=0⋅(5y-1)43
Rewrite the expression.
(5y-1)33-6(5y-1)43⋅(5y-1)43=0⋅(5y-1)43
(5y-1)33-6(5y-1)43⋅(5y-1)43=0⋅(5y-1)43
Divide 3 by 3.
(5y-1)1-6(5y-1)43⋅(5y-1)43=0⋅(5y-1)43
Simplify.
5y-1-6(5y-1)43⋅(5y-1)43=0⋅(5y-1)43
Cancel the common factor of (5y-1)43.
Tap for more steps…
Move the leading negative in -6(5y-1)43 into the numerator.
5y-1+-6(5y-1)43⋅(5y-1)43=0⋅(5y-1)43
Cancel the common factor.
5y-1+-6(5y-1)43⋅(5y-1)43=0⋅(5y-1)43
Rewrite the expression.
5y-1-6=0⋅(5y-1)43
5y-1-6=0⋅(5y-1)43
5y-1-6=0⋅(5y-1)43
Subtract 6 from -1.
5y-7=0⋅(5y-1)43
5y-7=0⋅(5y-1)43
Multiply 0 by (5y-1)43.
5y-7=0
5y-7=0
Solve the equation.
Tap for more steps…
Add 7 to both sides of the equation.
5y=7
Divide each term by 5 and simplify.
Tap for more steps…
Divide each term in 5y=7 by 5.
5y5=75
Cancel the common factor of 5.
Tap for more steps…
Cancel the common factor.
5y5=75
Divide y by 1.
y=75
y=75
y=75
y=75
The result can be shown in multiple forms.
Exact Form:
y=75
Decimal Form:
y=1.4
Mixed Number Form:
y=125
Solve for y (5y-1)^(-1/3)-6(5y-1)^(-4/3)=0

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top